KAJIAN MANAJEMEN RISIKO PADA PROYEK PENDIRIAN USAHA JASA KONSULTANSI BIDANG KONSTRUKSI DI KABUPATEN BANYUMAS - Dwi Sri Wiyanti (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2009)
Abstract Government departments in Banyumas district usually use a third party as Project planner and supervisor, therefore  consulting services are really needed. Moreover, nowadays  there are only 7 active consultants in Banyumas district. However, these opportunities do not guarantee the smooth process of establishment and survival of the company. There are things that can happen during the process of establishment and after the company running, which can not be predicted. For that purpose we need a study on risk management. After collecting data that relevant to the risk to be analyzed, economic analysis is used as a reference in identifying and determining the risk level and to find out the feasibility of a company established by calculating the NPV, IRR, BCR, and BEP. From the analysis of the feasibility study we can identify risks that might occur during the establishment of a company or at the time the company has been running up to reach the break event point. Furthermore identification that has been obtained are analyzed and quantified to determine the strategies that needed. From the calculation of engineering economic analysis it can be concluded that the risks that might occur greatly affect the value of NPV, IRR, and BCR to determine whether or not the company are feasible to establish. With the risk management review we can obtain strategies to face the risk of establishing consulting services for construction in Banyumas district.  Keywords: Risk Management, Consultancy Services, Banyumas District